The Construction of the Mediterranean Heritage: Croatian Case - Škrbić Alempijević, Nevena (2009)
In this paper the author approaches the concept of the Mediterranean as a cultural phenomenon. She points to a long tradition of rethinking and reinventing the Mediterranean. She also stresses that in Croatia strategies of self-stereotyping have an additional ideological dimension: break from socialism and “the Balkans”. She shows the complexity of these processes on the examples of the Croatian tourist industry advertisements and Croatian cultural politics. She concludes that the emphasis on the Mediterranean layer of the Croatian culture is an example of "selective traditions". The rediscovery of the Mediterranean in Croatia is not a transmission of centuries-old consciousness of our Mediterranean belonging ; it is an answer to contemporary needs, influenced by a specific political, economic and social context.
Projekt MZOS
ENG